Intracranial hypertension influence on the cerebral blood flow in children with serous meningitis - Yu. A. Rosin (Журнал инфектологии, 2014)
Transcranial Doppler sonography was performed in 120 children with serous meningitis with various degrees of intracranial hypertension. Cerebral blood flow disturbances – decreased dilatation reserve and mean blood flow velocity in cerebral arteries, increased cerebrovascularresistance were found.